Penerapan Upaya Peningkatan Kepercayaan Diri dan Kompetensi Mahasiswa Kebidanan dalam Keterampilan Klinis - Qorinah Estiningtyas Sakilah Adnani; Giyawati Yulilania Okinarum; Ari Indra Susanti; Lani Gumilang; Neneng Martini; Ade Zayu Cempaka Sari; Ira Nufus Khaerani (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
The midwife profession requires knowledge, competence, skills, and confidence so that they can provide professional services. The midwife profession requires knowledge, competence, skills, and confidence so that they can provide professional services. Competent and confident midwives can improve the quality of maternal and child health services. Mastery of competence and confidence possessed by prospective midwives in clinical practice is an important learning goal of the professional quality of graduates from health colleges, especially midwifery. The purpose of this activity is as an effort to increase the confidence of student midwives and midwives in carrying out their competencies. The method used is to hold a webinar and evaluate knowledge about the competence of midwives. This activity was held in 2 days with 740 registrants and the results showed that the average knowledge score of 317 participants increased by 0.74 from 4.82 to 5.56 with Pvalue=0.000. Midwifery Education Institutions and midwives can make the inosco instrument a measuring tool to determine the extent of the level of self-confidence possessed by prospective midwives and midwives to carry out their competence.